Inventory of Macroscopic Fungi in Oil Palm Plantations in Pantok West Borneo - Bonifasius, Bonifasius; Yeni, Laili Fitri; Fajri, Hayatul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Fungi are one of the abundant biodiversity both in Indonesia and in the world, so there are still many species of fungi that have not been successfully identified or known for their benefits. The purpose of this study was to determine the species of macroscopic fungi that can be collected in oil palm plantations in Pantok, West Kalimantan. This study used a qualitative approach, mushroom sampling using the plot method with roaming techniques, all species of macroscopic fungi found in oil palm plantations were recorded morphological characteristics and position of discovery in the observation sheet, then measured environmental factors, and the mushrooms obtained were preserved. Sample identification was carried out by matching morphologies including cup type and edges, cup color, stalk color and surface, stalk mounting type on the cup, and substrate. Using a mushroom identification book that refers to McKnight & McKnight (1987), Roberts & Shelley (2013), Moor and O'Sullivan (2014), and Laessoe (2013). The field data analysis used is descriptive analysis by describing the species of macroscopic fungi found in oil palm plantations. As for the data validity checking technique on the identification results using the website https://www.indexfungorum.org/ to see the validity of the scientific name of each fungus found. In this study there were 17 species of macroscopic fungi found, these fungi belonged to 1 phylum, namely the Basidiomycota phylum and consisted of 11 families, namely the Polyporaceae, Boletaceae, Entolomataceae, Ganodermataceae, Marasmiaceae, Omphalotaceae, Psathyrellaceae, Schizophyllaceae, Tricholomataceae, and Pluteaceae families. The environmental factors of this study were less favorable for fungal growth. From the results of this study it can be concluded that the diversity of fungi in oil palm plantations in Pantok, West Kalimantan is quite varied, this is influenced by environmental factors in the plantation.